Effect of MAP on shelf-life of broccoli and cabbage grown under natural farming - SHARMA, RAKESH; GAUTAM, SUNAKSHI; HAMID, HAMID (The Indian Journal of Agricultural Sciences, 2021)
An experiment was conducted to study the effect of modified atmosphere packaging (MAP) and storage conditions on the shelf-life and quality of broccoli and cabbage during 2019-20. For MAP, freshly harvested produce was packed in LDPE pouches (25.4 μm and 10 pin holes/100 cm2 area) was kept under ambient (17±2 C, RH 40-60%) and low temperature conditions (5±2oC, RH 90-95%) and shelf-life comparison was done on the basis of physiological loss in weight (PLW) at every alternate day up to 28 (broccoli) and 34 days (cabbage). Results revealed that broccoli and cabbage packed in perforated LDPE pouches and stored under low temperature storage retained higher sensory acceptability for 14-20 days with record extended shelf-life for market purpose up to 18 and 22 days, respectively with minimum PLW (